Explorations of the Syntax-Semantics Interface - Fleischhauer, Jens; Osswald, Rainer; Latrouite, Anja (Studies in Language and Cognition, 2021)
The articles in this volume present original research on the encoding of meaning in a variety of constructions and languages. Many of the contributions take the framework of Role and Reference Grammar as a point of reference, either by applying it to the analysis of linguistic data or by discussing, extending, and challenging some of its assumptions. The topics of the articles range from general questions concerning the relation of meaning and its syntactic realization to the study of specific grammatical phenomena in a number of typologically diverse languages, including Yucatec Maya, Kabardian, Tagalog, Murik-Kopar, Avatime, Whitesands, Tundra Yukaghir, and various Indo-European languages. The articles will be of interest to researchers and advanced students working on the interface between syntax, semantics and pragmatics.